Duodenal atresia in association with situs inversus abdominus - Raghu Shankar; Sadashiva P Rao; Kishan B Shetty (Wolters Kluwer Medknow Publications, 2012)
We report a rare association of duodenal atresia with situs inversus abdominus in a newborn. The infantogram revealed "reverse double-bubble sign" without dextrocardia. The sonography and echocardiography confirmed the diagnosis of situs inversus abdominus with multiple cardiac anomalies. Laparotomy and a duodenoduodenostomy were carried out.